DOI: 10.31274/rtd-180813-10324
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and ultrastructural aspects of the adaptation of Chlamydomonas reinhardtii to limiting CO2

Abstract: INFORMATION TO USERSThis manuscript has been reproduced from the microfilm master. UMI films the text directly from the original or copy submitted. Thus, some thesis and dissertation copies are in typewriter face, while others may be from any type of computer printer.The quality of this reproduction is dependent upon the quality of the copy submitted. Broken or indistinct print, colored or poor quality illustrations and photographs, print bleedthrough, substandard margins, and improper alignment can adversely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…After subcellular fractionation and isolation of intact mitochondria, Eriksson et al (1995) found that the 21-to 22-kDa polypeptide was associated with mitochondria of C. reinhardtii cells. In an independent study, Geraghty and Spalding (1995) also showed by immunogold labelling that LIP-21 is located in mitochondria. However, none of the low-CO2-inducible polypeptides have been linked to a specific function of the CCM (Spalding et al 1991).…”
Section: Introductionmentioning
confidence: 99%
“…After subcellular fractionation and isolation of intact mitochondria, Eriksson et al (1995) found that the 21-to 22-kDa polypeptide was associated with mitochondria of C. reinhardtii cells. In an independent study, Geraghty and Spalding (1995) also showed by immunogold labelling that LIP-21 is located in mitochondria. However, none of the low-CO2-inducible polypeptides have been linked to a specific function of the CCM (Spalding et al 1991).…”
Section: Introductionmentioning
confidence: 99%